[Memo from A J Stevens re: Californians for Common Sense] - STEVENS,AJ (Tufts Archival Research Center, 2007)
Memo from Arthur J Stevens informing recipients that Cal Calvert, Lorillard's Director of Employee Relations, will be attending a cocktail party hosted by Californians for Common Sense.